ЧЕРЕЗ 50 РОКІВ. ДО П’ЯТДЕСЯТИРІЧЧЯ ГОСПОДАРСЬКО-ПРАВОВОГО РУХУ В ДОНБАСІ - Mamutov, V.K. (Економіка та право, 2008)
The article describes recovery and progress of economic law science in the context of legal work in the industry and building of Donbas and of training lawyers for the national economy. It also illustrates the stages of this process in 1978–2008.